2018
DOI: 10.1097/md.0000000000013977
|View full text |Cite
|
Sign up to set email alerts
|

Could larger diameter of 4th generation ceramic bearing increase the rate of squeaking after THA?

Abstract: The present study aimed to evaluate the clinical outcomes and bearing-specific complications in a single center of 135 delta ceramic-on-ceramic (COC) total hip arthroplasties (THAs) and explore the occurrence rate of squeaking in 4th generation COC THAs and collate the risk factors for squeaking.We retrospectively analyzed consecutive cohorts of 127 patients (135 hips) who had primary THA with delta COC bearings in our hospital between April 2010 and April 2012. Preoperative Harris hip score (HHS), Western Ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…IL-6 gene is located in human chromosome 1q21 and is responsible for IL-6 production [ 9 ]. IL-6 is also an important pro-inflammatory factor that promotes cardiovascular disease, diabetes, and allergic reactions and affects the process of ovulation, implantation and fertilization [ 10 ]. CRP is encoded by CRP gene and is an acute‐phase protein that is synthesized in hepatocytes by IL-6 stimulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 gene is located in human chromosome 1q21 and is responsible for IL-6 production [ 9 ]. IL-6 is also an important pro-inflammatory factor that promotes cardiovascular disease, diabetes, and allergic reactions and affects the process of ovulation, implantation and fertilization [ 10 ]. CRP is encoded by CRP gene and is an acute‐phase protein that is synthesized in hepatocytes by IL-6 stimulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A summary of overall revision-free survival rates with alumina–zirconia couplings observed in four RCTs ( 38 , 39 , 40 , 41 ) and 14 cohort studies ( 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ) is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to data from the New Zealand Joint Registry collected between 1999 and 2015, the incidence of revision for CoC hips due to noise was 24/5587 (0.43%, 95% CI: 0.28–0.64%) ( 80 ). With an average follow-up of 6 years, raw numbers from 21 cohort studies ( 42 , 43 , 44 , 46 , 47 , 48 , 50 , 52 , 53 , 54 , 55 , 73 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ) and four RCT( 38 , 39 , 65 , 68 ) suggest an incidence of squeaking of 360/5658 (6.36%, 95% CI: 5.74–7.03%) and 9/321 (2.80%, 95% CI: 1.29–5.26%). Estimates from random-effects meta-analysis of proportions are 4.70% (95% CI: 2.27–7.89%) and 1.64% (95% CI: 0.04–4.67%), showing substantial heterogeneity (Supplementary Figure).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was 1 postoperative ceramic liner rim fracture and 13 hips had squeaking. Survival rate for revision was 98.5% at mean 70 months [ 34 ]. Aoude et al analyzed 133 consecutive THAs utilizing delta CoC.…”
Section: Discussionmentioning
confidence: 99%